Accounting Information System for Processing Zakat Funds at the North Sumatra National Amil Zakat Agency is Online Based - Zulita Gustika Sari (International Journal of Mechanical Computational and Manufacturing Research, 2023)
Zakat institutions are institutions that are in the midst of the public, so they are required to have transparency and accountability. In carrying out its activities as an amil, zakat processing organizations have principles that must be obeyed, including zakat processing organizations must have an accounting system and financial management. Audits, as well as publications. These three principles indicate that zakat fund management organizations must be transparent in carrying out their duties. This study aims to determine and examine the application of zakat accounting and accounting policies used by the national amil zakat agency. Provides an overview of the application of zakat accounting in the academic world. To solve this problem, the most effective solution is made, namely a web-based information system. In developing this application using the waterfall method. For the data flow method using UML (Unified Modeling Language) for data modeling using ERD (Entity Relationship Diagram) to describe the data model. With the development of this web-based information system, it aims to build a personal service process for institutions and facilitate the processing of zakat funds so that information regarding services and distribution is conveyed properly to institutions